Intra-left ventricular blood flow analysis to determine cardiac performance and dysfunction indices - Le, Thu Thao (2016)
Heart failure (HF) is one of the most common diseases in the developed world and is increasingly prevalent in developing countries, especially among the ageing population. It causes left ventricular (LV) dysfunction, involves high healthcare cost and has high mortality. Traditionally, HF patients were grouped into diastolic HF and systolic HF. However, these terms are now abandoned due to the fact that diastolic dysfunction exists in all symptomatic HF patients and systolic dysfunction, to a lesser extent, has been observed in diastolic HF. HF patients are currently stratified based on their LV ejection fraction (EF), which is a measure of systolic performance, into HF with preserved EF (HFpEF) and reduced EF (HFrEF). Although HFpEF is becoming prevalent, due to its complex mixture of diastolic and systolic dysfunction, as well as various degrees of LV remodelling, it remains a challenge to diagnose and provide pharmalogical therapies to HFpEF and thus, treatment and prognosis of HFpEF are mostly unaltered for the past 3 decades. With the advancement of non-invasive cardiac imaging modalities in recent years, cardiac haemodynamic information, which is crucial to diagnosis and disease management, can now be directly measured or derived without the need for invasive catheterization. In this thesis, intra-left ventricular flow was derived from echocardiographic colour Doppler flow images using vector flow mapping (VFM) technique. In chapter 3, intra-LV flow patterns of HF patients with different extent of diastolic and systolic dysfunction, as well as normal controls were described in both diastole and systole. From the flow information obtained using VFM, quantitative assessment of LV diastolic and systolic performance was then developed and applied to small groups of HF patients in the following chapters.